PERTUMBUHAN BIBIT KELAPA SAWIT ( Elaeis guineensis Jacq.) DENGAN MENGGUNAKAN MEDIA SEKAM PADI DAN FREKUENSI PENYIRAMAN DI MAIN NURSERY - Hermanto Hermanto; Ferry Ezra T. Sitepu; Jonatan Ginting (Universitas Sumatera Utara, 2014)
The growth of oil palm seedlings (Elaeis guineensis Jacq.) by the application of rice husk andfrequency of watering in the main nursery. This research aims to study aimed to determine thegrowth of oil palm seedlings to rice husk and watering frequency on the main nursery. This researchwas conducted in Greenhouses in the Faculty of Agriculture, University of North Sumatera, Medanwith ± 25 m altitude above sea level in January 2013 to April 2013 using a factorial randomizedblock design with two factors: Media planting rice husk (0:0, 2: 1, 1:1, 1:2) and watering frequency(1, 2, 3 days) parameters measured were plant height, stem diameter, number of leaves, total leafarea, fresh weight of seedlings, seedling dry weight. The results showed that treatment of rice huskgrowing media influence is not obvious to all treatment parameters. Watering frequency treatmentssignificantly affected stem diameter parameter 2 and 6 MST with the highest yield obtained in thetreatment of the frequency of watering every other day. Both treatment interaction effect was notsignificant on all treatments.Keywords: palm oil, rice husk, watering